Sistem Cerdas Sistem Bantu Pengenalan Awal Kesehatan Mental Pada Remaja Sekolah Menengah Pertama dengan Forward Chaining dan Certainty Factor - Nurpanto, Nugroho Wisma; Patmi Kasih (Nusantara of Engineering (NOE), 2025)
Adolescent mental health is a crucial issue that requires serious attention, especially at the junior secondary education level. Mental health disorders such as depression and anxiety often go undetected and have a negative impact on teenagers' lives. This research aims to develop an expert system that can provide an initial diagnosis of adolescent mental health using the Forward Chaining and Certainty Factor methods. This system is designed to support Guidance Counseling (BK) teachers in early detection of potential mental health problems, so that intervention can be carried out more quickly and precisely. The research methods used include data collection through observation and interviews at educational institutions as well as data analysis using a qualitative approach. The research results show that the expert system developed is able to provide an accurate initial diagnosis and can be used as a tool in dealing with adolescent mental health problems at school. It is hoped that the implementation of this system can reduce the number of mental health disorders in adolescents and improve their overall well-being.